Creative Industry-Based MSME Competitive Advantage Strategy in Padang City through Market Orientation and Product Innovation - Hesty Aisyah; M Tasnim; Sri Restu Ningsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The development of Micro, Small, and Medium Enterprises (MSMEs) is one of the economic driving forces that have an important role in the economy of Padang City because it contributes greatly to overcoming poverty and unemployment problems. MSMEs have many positive impacts, such as one of the expansion of labor absorption which makes it a place for low-income people to produce productive economic activities. MSMEs in Padang City are one type of business that can be resilient in various kinds of economic shocks so that from year to year the growth is always stable and consistent. This growth also affects the decline in unemployment, because MSMEs are labor-intensive businesses that require minimal Human Resources with a relatively small level of formal education and utilization of business capital. Although in terms of quantity, MSMEs in Padang City have increased, they are not accompanied by quality. This study aims to analyze the competitive advantage formed from the role of market orientation variables and product innovation in creative industry-based MSMEs in Padang City. The population in this study is creative industry business actors in Padang City applying purposive sampling techniques as a sampling. The conclusion of this reasearch are Based on the results of the study above on MSMEs in the city of Padang using SWOT analysis 4 quadrants, the position of MSMEs is at the growth stage. Based on analysis using IE matrix analysis, it is necessary to carry out a product development strategy, and Based on the results use SPACE matrix analysis, namely market and product development and product diversification.